FINANCING OF CRAFTS BUSINESS IN ENSURING THE DEVELOPMENT OF SMALL AND MEDIUM-SIZED ENTERPRISES - HARKUSHA, Yuliya (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the theoretical and methodological foundations of financing craft businesses. Models of financing craft businesses are highlighted, namely: self-financing, formal and informal financing. It is determined that self-financing occurs at the expense of equity, formal financing is provided through bank lending, non-bank financing, grants, preferential financing, venture funds. Informal attraction of additional resources involves direct financing of related parties, P2P financing, crowdfunding. Also, in the process of research, the characteristics of craft business from the point of view of financing were identified, namely: mainly represented by small and medium-sized enterprises, which determines the specifics of bank credit relations; non-serial production; high level of credit risk; business practically does not scale; franchising is not envisaged; insignificant turnover of the enterprise; low profitability of enterprises; low cost of inventories; combination of ownership and management functions; instability of demand for craft products. The results of the study indicate that bank credit remains a classic method of financing. The volume of loans provided to small and medium-sized enterprises, including craft enterprises, is actively growing. Craft enterprises also receive funds by participating in grant competitions, participating in international and national business support programs. Promising tools for financing craft activities are attracting venture capital, raising funds through crowdfunding platforms. The study also indicates that craft business is the basis for the development of local communities, the formation of a positive image of territorial associations, their investment environment, increasing the level of tourist attractiveness and a factor in economic growth in post-war recovery.
Keywords: craft business; small and medium businesses; entrepreneurship; financing; grants; investments